1995
DOI: 10.1021/ma00125a006
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Chain Orientation in Liquid Crystalline Polymers by Means of Microfocus X-ray Scattering Measurements

Abstract: A microfocus camera with a focus of 7 pm fwhm and a flux of 10u photons/s at the ESRF in Grenoble was used to investigate the microstructure of liquid crystalline polymer samples of 4-oxybenzoate-co-6-oxy-2-naphthoate (73:27) (Vectra A950 from Hoechst-Celanese). These samples show isotropic scattering when examined by means of a conventional X-ray camera with a large focus (2 mm). In melt-pressed thin films, we observed local variations of the direction of molecular orientation, which is due to the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…An alternative method of determining order parameter values has been provided by Lovell and Mitchell, who reported that the coefficients hP 2n i D of the orientational distribution function, D, expanded as evenorder Legendre polynomials, may be readily determined from the coefficients hP 2n i I of an equivalent expansion of the integrated intensity profile, I(χ), as given by Equation (6) [45]. This approach has seen widespread use in the field of liquid crystal elastomers [46][47][48][49][50][51][52][53][54][55], and is based on the same assumptions as the approaches described above, but instead of relating the molecular orientational distribution function to the scattering intensity profile, it directly relates their respective order parameters.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative method of determining order parameter values has been provided by Lovell and Mitchell, who reported that the coefficients hP 2n i D of the orientational distribution function, D, expanded as evenorder Legendre polynomials, may be readily determined from the coefficients hP 2n i I of an equivalent expansion of the integrated intensity profile, I(χ), as given by Equation (6) [45]. This approach has seen widespread use in the field of liquid crystal elastomers [46][47][48][49][50][51][52][53][54][55], and is based on the same assumptions as the approaches described above, but instead of relating the molecular orientational distribution function to the scattering intensity profile, it directly relates their respective order parameters.…”
Section: Introductionmentioning
confidence: 99%
“…SPM showed that for an untreated POCO surface, which had a microfibril structure, 0.3–0.4‐wide microfibrils met each other and fused into featureless amorphous regions [Fig. 7(a,b)] 12, 13. The POCO surface treated with remote and direct oxygen plasmas at 75 W for 60 s, as shown in Figure 7(c,d), showed many micropores 0.2–0.5 μm wide.…”
Section: Resultsmentioning
confidence: 99%
“…For WAXS experiments the high brilliance of thirdgeneration synchrotron radiation sources, such as the European Synchrotron Radiation Source (ESRF), has allowed the size of the X-ray beam at the sample to be reduced to micrometre and submicrometre levels. WAXS studies of polymeric systems now routinely use collimation systems (Dreher et al, 1995;Mahendrasingam et al, 1995) and capillary optics (Riekel et al, 1997;Martin et al, 1997) to produce beams of these dimensions. It has recently been shown that SAXS techniques can be employed in experiments with beams of a few micrometres in size, although the resolution was limited to about 15 nm (Riekel et al, 1998;Waigh et al, 1998).…”
Section: Introductionmentioning
confidence: 99%